Pengaruh penggunaan media video animasi terhadap motivasi - Ira Pratiwi; Mochamad Ridwan (Journal Of Sport Education (JOPE), 2021)
This study aims to determine how much-animated video media affects motivation to participate in learning physical education, sports, and health. The method used is a quasi-experimental method with a non-randomized control group pretest-posttest research design. The sample of this research is the students of class VII-C and VII-D SMP Negeri 20 Surabaya, totaling 51 students. The sample selection in this study was taken by using the probability sampling technique using random cluster sampling. The data collection process was carried out by giving a questionnaire through a google form distributed to the sample. The questionnaire contained the motivation to take part in learning physical education, sports, and health. The data analysis technique used the normality and homogeneity tests and the effect tests to determine the effect on the variables used. From the data processing results, it can be concluded that Ha is accepted, and the significant influence value is 38.3%. So it can be supposed that there is an effect of the use of animated video media on the motivation to take part in physical education, sports, and health.Copyright © The Author (s) 2021Journal of Sport Education (JOPE) is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.